Personal Factors, Motivation, and Their Impact on Patient Safety Culture Among Nurses - Santi Anugrahsari; Cicilia Windiyaningsih; Ahdun Trigono (Indonesian Journal of Global Health Research, 2026)
This study examined the role of personal factors and motivation in shaping patient safety culture. It employed a cross-sectional design with path analysis to assess the relationship between personal factors, motivation, and patient safety culture. Data were collected from 89 nurses from different hospital units using validated and reliable questionnaires. The measured variables included personal factors (knowledge, attitude, competence, and personality), motivation, and patient safety culture. The path analysis indicated that personal factors significantly affect motivation (p = 0.004, β = 0.897) and patient safety culture (p = 0.008, β = 0.940). Besides, motivation affects patient safety culture (p = 0.007, β = 0.315). Further, motivation mediates the relationship between personal factors and patient safety culture (indirect effect = 0.282, total effect = 1.222). Therefore, personal factors play a significant role in shaping the culture of patient safety, either directly or indirectly. High motivation could increase adherence to patient safety protocols. Hospitals need to evaluate the personal factors of healthcare workers, such as their competence, training, experience, and understanding of patient safety, to build a culture of patient safety. Furthermore, strategies to increase motivation are needed.